Progressive multifocal leukoencephalopathy and black fungus in a patient with rheumatoid arthritis without severe lymphocytopenia - de Regt, Marieke J. A. (JMM Case Rep, 2016)
INTRODUCTION: Progressive multifocal leukoencephalopathy (PML) is a rare demyelinating brain infection caused by JC polyomavirus (JCV), primarily seen in patients with severely compromised cellular immunity. Clinical presentation varies depending on the affected white matter. PML prognosis is variable and effective treatments are lacking. CASE PRESENTATION: A 75-year-old Chinese woman with type 2 diabetes mellitus, chronic kidney disease and rheumatoid arthritis, treated with low-dose methotrexate and prednisolone for 2.5 years, developed a Pleurostomophora richardsiae infection of her left arm. After 6 months of treating this rare black fungus infection with voriconazole, surgery and immunosuppression discontinuation, she presented with progressive afebrile encephalopathy with right-sided hemiparesis. There were no signs of inflammation or metabolic abnormalities. Brain magnetic resonance imaging revealed diffuse frontal white matter lesions and a cerebrospinal fluid PCR confirmed PML due to JC virus. Severe lymphopenia was never present, and at PML diagnosis, CD4 and CD8 T-cell counts were 454 mm(−3) and 277 mm(−3). CD8 T-cells were able to respond to JCV VP1 peptide stimulation with TNFα secretion. Peripheral B-cell count was only 8 mm(−3). Mirtazapine and Maraviroc were started, but unfortunately, she rapidly deteriorated and died 5 weeks after PML diagnosis. CONCLUSION: Although peripheral lymphocyte counts were never low and CD4 T-cell count was close to normal, the persistent black fungus infection was a hallmark of severely compromised cellular immunity. The unexpected extremely low absolute B-cell count might suggest a protective role for B-cells. The paradoxical, clinical PML onset months after immunosuppressive discontinuation suggests that it was only discovered in the context of an immune reconstitution inflammatory syndrome.